Synthesis and Crystal Structure of Zr3V3GeSn4 - Daniel Parks; Karim Niang; Yuri Janssen; Jack W. Simonson (Crystals, 2023)
Quantum fluctuations inherent in electronic systems positioned close to magnetic instabilities can lead to novel collective phenomena. One such material, <semantics>β</semantics>-Ti<semantics>6</semantics>Sn<semantics>5</semantics>, sits close to ferromagnetic (FM) instability and can be pushed to an itinerant FM-ordered state with only minute magnetic or non-magnetic doping. The binary nature of this compound, however, limits the tuning variables that can be applied to study any emergent physics, which are likely to be sensitive to the introduction of chemical disorder.Accordingly, we grew high-quality single crystals of a new quaternary compound Zr<semantics>3</semantics>V<semantics>3</semantics>GeSn<semantics>4</semantics> from a Sn-rich self flux, and determined the structure with single-crystal X-ray diffraction. Zr<semantics>3</semantics>V<semantics>3</semantics>GeSn<semantics>4</semantics> forms in an ordered derivative of the hexagonal <semantics>β</semantics>-Ti<semantics>6</semantics>Sn<semantics>5</semantics> structure with Zr and V atomic positions that show no indication of site interchange. Ge likewise occupies a single unique atomic position. The V site, which would be the one most likely to give rise to any magnetic character, is located at the center of a distorted octahedron of Sn, with such octahedra arranged in face-sharing chains along the crystallographic c axis, while the chains themselves are organized in a kagome geometry. Zr<semantics>3</semantics>V<semantics>3</semantics>GeSn<semantics>4</semantics> represents the second known quaternary phase within this system, suggesting that other compounds with this structure type await discovery.